Pengaruh Zat Pengatur Tumbuh dari Sampah Rumah Tangga sebagai Media Tanam Krisan (Dendranthema grandiflora Tzvelev.) secara In Vitro - Royani, Ida; Imran, Ali; Dharmawibawa, Iwan Doddy (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to: 1) obtain growth regulators that are easy to obtain at low prices, because synthetic growth regulators are relatively expensive for novice researchers and are very difficult to obtain; and 2) to find out whether household waste can be used as a plant growth regulator in vitro which has been widely used and has been successful conventionally in several types of plants. The method used in this study was experimental, using a completely randomized design (CRD) with three replications. The media used was MS media by adding growth regulators from household waste with a concentration of (0-3) mg/L. The parameters in this study were the number of shoots and roots. The data obtained were then analyzed qualitatively, because the resulting data was not normal and not homogeneous. The results showed that the highest number of shoots was at a concentration of 2 mg/L organic waste growth regulator, with 5 shoots and 15.7 roots, with 8 days after planting on chrysanthemum growing media.